Proceedings of the 37th Annual International Symposium on Computer Architecture 2010
DOI: 10.1145/1815961.1815998
|View full text |Cite
|
Sign up to set email alerts
|

An integrated GPU power and performance model

Abstract: GPU architectures are increasingly important in the multi-core era due to their high number of parallel processors. Performance optimization for multi-core processors has been a challenge for programmers. Furthermore, optimizing for power consumption is even more difficult. Unfortunately, as a result of the high number of processors, the power consumption of many-core processors such as GPUs has increased significantly. Hence, in this paper, we propose an integrated power and performance (IPP) prediction model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
218
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(227 citation statements)
references
References 21 publications
(13 reference statements)
2
218
0
Order By: Relevance
“…The read/write times to CMOS-and TFET-based registers and the total execution time are collected from the modified GPGPU-Sim to evaluate both RF dynamic and leakage energy consumption. Our energy estimation is consistent with previous studies [3,4,8].…”
Section: Evaluations 41 Experimental Methodologysupporting
confidence: 92%
See 1 more Smart Citation
“…The read/write times to CMOS-and TFET-based registers and the total execution time are collected from the modified GPGPU-Sim to evaluate both RF dynamic and leakage energy consumption. Our energy estimation is consistent with previous studies [3,4,8].…”
Section: Evaluations 41 Experimental Methodologysupporting
confidence: 92%
“…Accessing such sizeable register files leads to massive power consumption [2][3][4][5][6]. It has been reported that the register files consume 15%-20% of the GPU stream multiprocessor's power [8]. Effectively optimizing the register files power consumption is critical and the first step towards the energy-efficient GPUs.…”
Section: Introductionmentioning
confidence: 99%
“…We use average power P to substitute P(t) and estimate the energy consumed. So E is a sum of product of average power , and T obtained by the performance counter, namely EPT =× [9] .…”
Section: Power Modelmentioning
confidence: 99%
“…Hong and Kim [30] propose an integrated GPU power and performance analysis model which can be applied without performance measurements. Zhang [43] and Chen [21] use similar strategies to statistically correlate the GPU power consumption and its execution behaviors.…”
Section: Related Workmentioning
confidence: 99%